Multibahasa dalam Konteks Global: Pendidikan, Ekonomi, dan Budaya - Satunggale Kurniawan; Chusnul Chabibah Ilhama (Postgraduate Program UIN Sultanah Nahrasiyah Lhokseumawe, 2026)
This study examines multilingualism as a defining feature of globalization and analyzes its roles across education, economic development, and cultural interaction. Using a qualitative descriptive approach based on a systematic literature review, the research synthesizes findings from academic publications, policy documents, and international reports. The results indicate that multilingual education enhances critical thinking, metalinguistic awareness, and intercultural competence through approaches such as translanguaging. In the economic domain, multilingualism functions as valuable human capital, increasing employability, productivity, and global competitiveness. From a cultural perspective, multilingualism enriches identity formation and facilitates cross-cultural exchange, although it also raises concerns about the dominance of global languages and the marginalization of local linguistic diversity. Additionally, digital technologies accelerate multilingual communication while simultaneously contributing to linguistic inequality. The study concludes that effective multilingual policies must balance global integration with the preservation of local languages and cultural identities. An interdisciplinary approach is essential to ensure that multilingualism serves as a tool for inclusive development and sustainable global engagement.